Generasi Muda dan Krisis Kewarganegaraan Politik: 1. Bentuk dan Indikasi Krisis Kewarganegaraan pada Generasi muda 2. Faktor-Faktor Penyebab Krisis Kewarganegaraan 3. Dampak Krisis Kewarganegaraan terhadap Kehidupan Berbangsa dan Bernegara 4. Peran Lembaga Pendidikan, Media, dan Lingkungan Sosial 5. Upaya dan Solusi untuk Meningkatkan Kesadaran Kewarganegaraan pada Generasi Muda - Desri Noer Laily; Emilia Susanti; Septi Dwi Ilva; Wayan Mayuda (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The young generation plays an important role in the sustainability of democracy in Indonesia, but they show a significant apathy towards political participation, which causes a crisis of political citizenship as seen from the decline in awareness and involvement in the democratic process. Studies show that a number of young voters have low interest in elections, doubt political institutions, and are influenced by misinformation on social media. The education system has been less successful in building critical political awareness and a sense of civic responsibility among young people. Factors causing this crisis include a lack of role models, the spread of ethnocentrism, and misunderstandings of democracy, in addition to the external influence of globalization that erodes national identity. The resulting passivity can threaten the integrity of democracy and the progress of society. To solve this problem, strategic interventions involving educational institutions, the media, and the social context are crucial. Improving civic education, encouraging media literacy, and building constructive social discussions can restore political engagement among the young generation. Cooperation between various parties is needed to develop responsible citizenship and empower the young generation to actively participate in the future of the country.